Pengaruh Perbedaan Fishing Ground 711 dan 712 terhadap Hasil Tangkapan Cumi-Cumi (Loligo spp) dengan Jala Jatuh Berkapal di Pelabuhan Perikanan Nusantara Muara Angke Jakarta - Anggi Kezia Maranatha Simbolon; Achmad Kusyairi; Exist Saraswati (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
This study aims to analyze the effect of fishing ground differences between WPPNRI 711 and 712 on squid (Loligo spp) catches using boat-operated falling nets landed at Nusantara Fishing Port Muara Angke, Jakarta. The research employed a quantitative approach with a two-treatment experimental design, involving fishing operations in two different areas with an equal number of trips (six trips each), analyzed using an independent samples t-test. The results indicated no statistically significant difference in catches between WPPNRI 711 and 712 (p = 0.747 > 0.05). However, production data revealed variations in catch differences, with CPUE (Catch Per Unit Effort) in WPP 711 being higher than in WPP 712. These variations are likely influenced by environmental factors, oceanographic conditions, fishing pressure, and squid spawning seasons. The implications of this study highlight that differences in fishing grounds do not always produce significant statistical impacts on catches but remain crucial for sustainable squid fisheries management. Policy recommendations include regulating fishing efforts based on spawning seasons, routine stock monitoring through CPUE, and adopting advanced fishing technologies to enhance efficiency and sustainability. This research provides valuable input for fisheries management and supports sustainable utilization of squid resources at Muara Angke.